A Novel Prognostic Scoring Model for Myelodysplastic Syndrome Patients With SF3B1 Mutation - Ma, Liya; Liang, Bin; Hu, Huixian; Yang, Wenli; Lin, Shengyun; Cao, Lihong; Li, Kongfei; Kuang, Yuemin; Shou, Lihong; Jin, Weimei; Lan, Jianping; Ye, Xingnong; et al. (Frontiers in Oncology, 2022)
The outcomes of myelodysplastic syndrome (MDS) patients with SF3B1 mutation, despite identified as a favorable prognostic biomarker, are variable. To comprehend the heterogeneity in clinical characteristics and outcomes, we reviewed 149 MDS patients with SF3B1 mutation in Zhejiang province of China. Eighty (53.7%) patients diagnosed as MDS with ring sideroblasts (MDS-RS) following the 2016 World Health Organization (WHO) classification and 125 (83.9%) patients belonged to lower risk following the revised International Prognostic Scoring System (IPSS-R). Although clonal hematopoiesis-associated mutations containing TET2, ASXL1 and DNMT3A were the most frequent co-mutant genes in these patients, RUNX1, EZH2, NF1 and KRAS/NRAS had significant effects on overall survival (OS). Based on that we developed a risk scoring model as IPSS-R×0.7+RUNX1×0.4+EZH2×0.5+RAS×1.0+NF1×1.2. Patients were categorized into two subgroups: low-risk (L-R, score < 2.65) group and high risk (H-R, score ≥ 2.65) group. The 3-year OS for the L-R and H-R groups was 92% (95% CI, 84%-100%) and 36% (95% CI, 19%-54%), respectively (P<0.001). This proposed model distinctly outperformed the widely used IPSS-R. In summary, we constructed and validated a personalized prediction model of MDS patients with SF3B1 mutation that can provide survival probability at diagnosis and in the course of a patient’s disease.